2019
DOI: 10.1016/j.wocn.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of early experience and continued language use in bilingual speech production: A study of Galician and Spanish mid vowels by Galician-Spanish bilinguals

Abstract: This is a repository copy of The role of early experience and continued language use in bilingual speech production: A study of Galician and Spanish mid vowels by Galician-Spanish bilinguals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
0
4
0
4
Order By: Relevance
“…Both found that only Galiciandominant bilinguals distinguished Galician-specific front and back mid vowel categories, while Spanish-dominant bilinguals, and in the case of Tomé Lourido and Evans (2018) also Galician new speakers, so-called neofalantes, largely merged them. In contrast, Mayr et al (2019a) reported merged mid vowel categories even for Galician-dominant bilinguals from Galician-speaking homes with continuous high use of the language. The authors argued that in addition to cognitive factors, neutralization is likely a result of inconsistent input and socioindexical factors.…”
Section: Introductionmentioning
confidence: 78%
“…Both found that only Galiciandominant bilinguals distinguished Galician-specific front and back mid vowel categories, while Spanish-dominant bilinguals, and in the case of Tomé Lourido and Evans (2018) also Galician new speakers, so-called neofalantes, largely merged them. In contrast, Mayr et al (2019a) reported merged mid vowel categories even for Galician-dominant bilinguals from Galician-speaking homes with continuous high use of the language. The authors argued that in addition to cognitive factors, neutralization is likely a result of inconsistent input and socioindexical factors.…”
Section: Introductionmentioning
confidence: 78%
“…En xeral, o conxunto destes traballos mostra que hai unha relación positiva clara entre o grao de dominio en galego e a produción de dous dos contrastes fonolóxicos, /e/-/ɛ/ e /o/-/ɔ/, que diferencian o vocalismo galego do castelán. Con todo, os resultados de López-Bueno (2017) e Mayr et al (2019) reflicten un posible cambio no sistema vocálico do galego tradicional que afecta a unha parte importante dos galegofalantes das súas mostras, segundo o cal estas oposicións xa non son realizadas polos falantes prototípicos de galego. As asimetrías existentes nos resultados proporcionados por estas investigacións poñen de relevo a necesidade de afondar nas descricións experimentais do sistema fonético-fonolóxico do galego, así como no efecto que ten o contacto co español sobre a variación existente no plano fónico.…”
Section: O Efecto Do Contacto De Linguas No Vocalismo Galegounclassified
“…Pese a que os resultados deste estudo deben ser tomados con cautela, debido ao tamaño da mostra e ao grupo de falantes no que se basea este traballo, si mostran unha tendencia á converxencia do vocalismo galego do castelán. Con todo, a existencia doutros traballos con resultados semellantes, como o de Mayr et al (2019), apoia a validez dos nosos resultados. Os resultados de ambos os dous traballos corroboran que este sistema "innovador" está presente, polo menos, en contextos e usos formais de galego.…”
Section: Conclusiónsunclassified
See 2 more Smart Citations